Correction: Ordered nanoparticle arrays interconnected by molecular linkers: electronic and optoelectronic properties. (28th November 2014) - Liao, Jianhui; Blok, Sander; van der Molen, Sense Jan; Diefenbach, Sandra; Holleitner, Alexander W.; Schönenberger, Christian; Vladyka, Anton; Calame, Michel
Abstract : Correction for 'Ordered nanoparticle arrays interconnected by molecular linkers: electronic and optoelectronic properties' by Jianhui Liao et al., Chem. Soc. Rev., 2015, DOI: ; Web:10.1039/c4cs00225c .